Optimizing the Performance of the Gakkum Unit of the Jepara Police Traffic Unit in Using ETLE to Reduce the Number of Violations of Two-Wheeled Vehicles (Indonesian Journal of Police Studies, 2024)
In the implementation of ETLE Mobile Hand Held in Jepara Regency, it can monitor negligence and disobedience of commUnity rules with various needs and interests for mobilization on the highway. ETLE Mobile Hand Held is still relatively new because it has only been operating for 12 months and there is still a need for adaptation from people who are accustomed to conventional tickets to become accustomed to electronic tickets. the majority of people do not understand the ETLE mechanism works.The problem formulated in this final project is to find out how to optimize the performance and efforts of the Gakkum Unit in the use of ETLE to reduce the number of violations of two-wheeled vehicles and also to add knowledge and repertoire that can be used as a reference for further research.The theories and concepts that the author uses as a problem analysis knife are management theory and SWOT theory. From the research conducted, it was concluded that the performance of the Gakkum Unit of the Jepara police traffic Unit found that the activity plan that had been made was not implemented optimally. The AAP given by the leadership of the Unit and the Unit is not carried out effectively by members. Lack of understanding of members of the Jepara police Satlantas regarding the job deks they carry out. In organizing there is not the right placement of members of the Jepara police Satlantas in accordance with the competencies of certain members. In the Gakkum Unit, in the field of subnit dakgar there are only 2 members, which means that it still requires additional personal. At the implementation stage, it was found that ETLE Mobile Hand Held did not cover all traffic violations and only certain traffic violations could be captured by ETLE Mobile Hand Held. There is no ETLE Static and ETLE Mobile on board yet. Lack of supporting devices for ETLE Mobile Hand Held. In supervision Members do not follow the tasks ordered at the planning stage submitted by Unit and Unit leaders in the AAP.
Keywords: ETLE , Unit Gakkum , Optimalisasi , Pelanggaran Lalu Lintas